POLITICAL MECHANISM IN THE REALIZATION OF SUSTAINABLE DEVELOPMENT GOALS IN THE SYSTEM OF LOCAL GOVERNMENT - Микола БОГАЧЕНКО (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The study aims to analyze the political mechanisms essential for the effective realization of Sustainable Development Goals (SDGs) within the local government framework. The research employs a mixed-method approach, combining qualitative and quantitative analyses to evaluate the interaction between local self-government bodies (LSGs) and businesses, improving investment resources, and directing investment capital towards human resources. The study reveals that the peculiarities of implementing SDGs in Ukraine involve ensuring the stabilizing and distributive functions of the state, which contribute to stimulating economic growth and efficient resource allocation. A new paradigm of local self-government is proposed, characterized by minimal state intervention in regional economies. The results highlight the importance of decentralization and the empowerment of local authorities, aiming to enhance the efficiency and responsiveness of local governance. The study identifies that fostering closer collaboration between local governments and businesses creates a conducive environment for economic development and innovation. Human capital development, through directing investment capital towards education, training, and skill development, is found to enhance the productivity and competitiveness of the local workforce, attracting more investment and creating new job opportunities. The research underscores the significance of international cooperation in achieving SDGs, encouraging local enterprises to engage in international projects and partnerships to leverage global expertise and resources. Innovative financing mechanisms, including public-private partnerships and impact investing, are proposed to support local development initiatives, aiming to reduce dependency on state budgets and enhance financial sustainability. Theoretical implications suggest that the proposed model can be applied to other regions with similar economic and governance structures. Practically, the study offers actionable insights for policymakers and local governments to design strategies for sustainable local development. The originality of the research lies in its comprehensive approach, integrating political, economic, and social dimensions of sustainable development at the local level. Further research should explore the long-term impacts of these mechanisms and address potential limitations related to varying regional contexts. This empirical study provides a foundation for future studies on sustainable development in local governance.